PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN RUMAH SAKIT JIWA TAMPAN PEKANBARU - Yelpi Yelpi; Nuryanti Nuryanti; Roesdi Rosnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research was conducted at Rumah Sakit Jiwa Tampan Pekanbaru. The purpose of this study was to determine the effect of variable work discipline, motivation, and organizational commitment partially or simultaneously on the performance of employee Rumah Sakit Jiwa Tampan Pekanbaru. The study population was all employees of 49 people and the number of samples was done by census, which made the entire population in to a sample 49 employees. The research variables used were work discipline, motivation, and organizational commitment as independent variables and employee performance as the dependent variable. The data analysis method used is descriptive analysis and multiple linear regression analysis using SPSS 23.0 for Windows. The results of the study concluded that work discipline, motivation, and organizational commitment partially or simultaneously had a significant effect on employee performance. The result of the calculation of the coefficient of determination (R2) is equal to 0.590 which means that motivation, job satisfaction, and organizational commitment can explain the variable employee performance by 59%, while the remaining 41% is influenced by other variables not examined in this study.Keywords : Work Discipline, Motivation, Organizational Commitment, and Employee Performance.